Pan-Genome-Wide Identification and Transcriptome-Wide Analysis of DREB Genes That Respond to Biotic and Abiotic Stresses in Cucumber - Can Wang; Jing Han; Ting Wang; Chunhua Chen; Junyi Liu; Zhixuan Xu; Qingxia Zhang; Lina Wang; Zhonghai Ren (Agriculture, 2022)
The production of cucumber (Cucumis sativus L.) is often harmed by biotic and abiotic stresses. Although the dehydration-responsive element-binding (DREB) transcription factors, playing vital roles in stress responses, have been characterized in several plant species, little is known about the pan-genome characteristics of DREB genes and their expression patterns under different stresses in cucumber. In this study, we identified 55 CsDREBs from the cucumber pan-genomes of 13 accessions, but only four accessions had all the genes. Most of the CsDREB proteins had sequence length and/or amino acid variations, and only four of them had no variation among different accessions. Using the 55 CsDREBs from ‘9930’, we analyzed their gene structures, conserved domains, phylogenetic relationships, gene promoter’s cis-elements and syntenic relationships, and classified them into six groups. Expression pattern analysis revealed that eight CsDREBs showed constitutive expression (FPKM > 1 in all samples), and different CsDREBs showed specifically high expression in root, stem, leaf, tendril, male-flower, female flower, and ovary, respectively, suggesting that these genes might be important for morphogenesis and development in cucumber. Additionally, a total of 31, 22, 30 and nine CsDREBs were differentially expressed in responding to the treatments of heat, NaCl and/or silicon, power mildew and downy mildew, respectively. Interestingly, CsDREB33 could respond to all the tested stresses. Our results provide a reference and basis for further investigation of the function and mechanism of the DREB genes for resistance breeding in cucumber.